2016
DOI: 10.1038/srep37764
|View full text |Cite
|
Sign up to set email alerts
|

Highly Bendable In-Ga-ZnO Thin Film Transistors by Using a Thermally Stable Organic Dielectric Layer

Abstract: Flexible In-Ga-ZnO (IGZO) thin film transistor (TFT) on a polyimide substrate is produced by employing a thermally stable SA7 organic material as the multi-functional barrier and dielectric layers. The IGZO channel layer was sputtered at Ar:O2 gas flow rate of 100:1 sccm and the fabricated TFT exhibited excellent transistor performances with a mobility of 15.67 cm2/Vs, a threshold voltage of 6.4 V and an on/off current ratio of 4.5 × 105. Further, high mechanical stability was achieved by the use of organic/in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Kim and Münzenrieder et al reported that the threshold voltage in Figure 14b and the TFT mobility in Figure 14c shifted to opposite directions under compressive and tensile strain [81]. The results of the repeatability tests with four forms are shown in Figure 13a-d [160]. In Figure 13a, b the TFTs were bent along the channel width at a bending radius of 3 mm and 1.5 mm, respectively.…”
Section: Degradation Of Tfts Under Mechanical Stressmentioning
confidence: 91%
See 4 more Smart Citations
“…Kim and Münzenrieder et al reported that the threshold voltage in Figure 14b and the TFT mobility in Figure 14c shifted to opposite directions under compressive and tensile strain [81]. The results of the repeatability tests with four forms are shown in Figure 13a-d [160]. In Figure 13a, b the TFTs were bent along the channel width at a bending radius of 3 mm and 1.5 mm, respectively.…”
Section: Degradation Of Tfts Under Mechanical Stressmentioning
confidence: 91%
“…In this section, the bending behaviors of strained TFTs are discussed. Figure 12 shows two kinds of bending behaviors of IGZO TFTs [160]. In Figure 12a, the TFT was bent along with the channel width, while the TFT in Figure 12b was bent along with the channel length.…”
Section: Degradation Of Tfts Under Mechanical Stressmentioning
confidence: 99%
See 3 more Smart Citations